2011
DOI: 10.1176/appi.ajp.2011.11020281
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Volume Abnormalities in ADHD: Voxel-Based Meta-Analysis Exploring the Effects of Age and Stimulant Medication

Abstract: These findings confirm that the most prominent and replicable structural abnormalities in ADHD are in the basal ganglia. They furthermore suggest that ADHD patients may progressively catch up with their developmental delay with advancing age and that use of stimulant medication may be associated with normalization of structural abnormalities in ADHD, although longitudinal studies are needed to confirm both observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

51
443
8
21

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 532 publications
(523 citation statements)
references
References 65 publications
51
443
8
21
Order By: Relevance
“…13 Two of the VBM meta-analyses mentioned previously found that subcortical volume differences between patients with ADHD and controls were smaller when the patients had taken medication. 6,7 Further, increasing age was found to be associated with smaller brain volume differences 6,7 between participants with ADHD and controls, which is in line with the findings of studies reporting delayed brain maturation in participants with ADHD. 2,14 As previous MRI studies of ADHD included mostly children or adults, 5-7 the present study adds to the literature by focusing on adolescents and young adults.…”
Section: Introductionsupporting
confidence: 86%
See 4 more Smart Citations
“…13 Two of the VBM meta-analyses mentioned previously found that subcortical volume differences between patients with ADHD and controls were smaller when the patients had taken medication. 6,7 Further, increasing age was found to be associated with smaller brain volume differences 6,7 between participants with ADHD and controls, which is in line with the findings of studies reporting delayed brain maturation in participants with ADHD. 2,14 As previous MRI studies of ADHD included mostly children or adults, 5-7 the present study adds to the literature by focusing on adolescents and young adults.…”
Section: Introductionsupporting
confidence: 86%
“…28 However, findings in the prefrontal cortex have been inconsistent and are not supported by meta-analyses. [5][6][7] A possible contributing factor is the heterogeneity in age among studies, as development of the prefrontal cortex is late and protracted. 21 Subtyping of ADHD has been proposed based on dorsalfrontostriatal, orbitofrontal-striatal and fronto-cerebellar circuits involved in cognitive control, reward and motivation, and timing and building temporal expectations, respectively.…”
Section: J Psychiatry Neurosci 2016;41(4)mentioning
confidence: 99%
See 3 more Smart Citations